Symptoms of an Unruly Age : Li Zhi and Cultures of Early Modernity - Handler-Spitz, Rebecca (Book collections on Project MUSE., 2017)
Symptoms of an Unruly Age compares the writings of Li Zhi (1527-1602) and his late-Ming compatriots to texts composed by their European contemporaries, including Montaigne, Shakespeare, and Cervantes. Emphasizing aesthetic patterns that transcend national boundaries, Rivi Handler-Spitz explores these works as culturally distinct responses to similar social and economic tensions affecting early modern cultures on both ends of Eurasia. The paradoxes, ironies, and self-contradictions that pervade these works are symptomatic of the hypocrisy, social posturing, and counterfeiting that afflicted both Chinese and European societies at the turn of the seventeenth century.